INOVASI PEMASARAN DIGITAL KELOMPOK GSH_MOROSUNGGINGAN GUNA PENINGKATAN EKONOMI KELUARGA - Chusnul, Rofiah; Mardi, Astutik; Primaadi , Airlangga (COMVICE: Journal Of Community Service, 2024)
Morosunggingan Village in Jombang Regency faces socio-economic problems in the form of poverty and high rates of stunting and malnutrition in pregnant women and children. The Srikandi Women's Group, as a fostered partner, tries to overcome these problems through hydroponic businesses but faces obstacles in terms of business management and marketing. The Community Service Program funded by Ministry of Education, Culture, Research, and Technology in 2024, was implemented by a team of lecturers from STIE PGRI Dewantara and Wahab Hasbullah University from August to October 2024. The solutions offered include financial management training, digital marketing through social media, and the implementation of a digital application-based financial recording system. This activity has succeeded in increasing managerial capacity, expanding marketing reach, and supporting nutrition programs for stunted children and pregnant women. The impact of this program can be seen in the increase in group income and the decrease in stunting rates in the village. The follow-up plan includes ongoing assistance in product diversification and strengthening digital marketing to ensure the sustainability of the fostered partner's business.